'I want to make myself useful': the value of nature-based adult day services in urban areas for people with dementia and their family carers. Issue 3 (14th March 2021) - de Bruin, Simone R.; Buist, Yvette; Hassink, Jan; Vaandrager, Lenneke
Abstract: Nature-based adult day services (ADSs) in urban areas are relatively new services in the Netherlands. Since knowledge about these services is still scarce, this study aimed to elucidate their value for people with dementia and their family carers in terms of health and wellbeing. We interviewed 39 people with dementia attending nature-based ADSs in urban areas and their family carers, and 17 providers of these services. Respondents indicated that nature-based ADSs in urban areas positively affected the health and wellbeing of people with dementia. According to them, these services support contact with nature and animals, activity engagement, physical activity, structure, social interactions, healthy eating, a sense of meaning in life and a focus on normal daily life. Respondents further indicated that these services stimulate respite, reassurance and maintenance of family carers' own activities and social contacts. We conclude that nature-based ADSs in urban areas have a wide range of benefits that might affect the health and wellbeing of people with dementia and their family carers. Worldwide, demand is growing for innovative practices in dementia care. It is therefore worthwhile monitoring the development of dementia care innovations, such as nature-based ADSs, and for countries to exchange lessons learned from these services.